Strategic Planning for Micro-Companies in an Uncertain Business Environment Using AI-Based Technology - Terpelle, Chris (Digital Repository of Theses - SSBM Geneva, 2025)
This thesis explores how Artificial Intelligence (AI) can enhance strategic planning for micro-companies operating in uncertain business environments. Micro-companies, which constitute the majority of businesses in the Netherlands, often lack the time, financial resources, strategic knowledge, or motivation to engage in formalized strategic planning. Existing strategic frameworks are often too complex or abstract for micro-businesses, particularly owner-managed enterprises (OMEs) whose primary goals may be survival, autonomy, or social value rather than growth. The research draws upon the concept of bounded rationality to argue that micro-entrepreneurs make decisions under severe cognitive and informational constraints. It proposes that AI, when used as a cognitive enabler rather than a decision-maker, can help overcome these limitations by offering structure, clarity, and analytical support. Using a Design Science Research (DSR) and Action Research methodology, the study develops and tests a customized twelve-step strategic planning process embedded in an AI-supported digital tool. The tool was iteratively designed and evaluated with micro-company owner-managers through surveys and prototype testing using a low-code platform. Findings indicate that participants acknowledged the value of structured planning when presented in a practical, non-intimidating format enabled by AI. The tool significantly improved users’ confidence, enhanced strategic planning literacy, and improved their ability to articulate long-term goals. Features associated with Explainable AI (XAI), such as the tool’s ability to justify recommendations based on market data and user input, played a crucial role in building trust and enabling learning. The study demonstrates that strategic planning can be democratized for micro-enterprises through intuitive, adaptive, and explainable AI-driven tools. This research contributes to the theory by extending the application of bounded rationality and combining deliberate and emergent strategies in the context of digital tools for strategic planning. Practically, it provides actionable insights for software developers, policymakers, and support organizations seeking to enhance strategic engagement among micro-enterprises. It concludes with recommendations for future research to explore long-term impacts and ethical considerations in AI-supported strategic decision-making.